Visceral Fat Accumulation, Insulin Resistance, and Elevated Depressive Symptoms in Middle-Aged Japanese Men - Yamamoto, Shuichiro (PLoS One, 2016)
OBJECTIVE: To investigate visceral fat accumulation and markers of insulin resistance in relation to elevated depressive symptoms (EDS). METHODS: Participants were 4,333 male employees (mean age, 49.3 years) who underwent abdominal computed tomography scanning, measured fasting insulin, and did not self-report diabetes and mental disorders under treatment and history of cancer, myocardial infarction, and stroke. Multivariable logistic regression was used to assess the association of EDS with abdominal fat deposition and markers of insulin resistance. RESULTS: Visceral fat area (VFA) and fasting insulin were significantly, positively associated with EDS. Multivariable-adjusted odds ratios (95% confidence interval) of high VFA for the lowest through highest quartile of depression score were 1 (reference), 1.18 (0.97–1.42), 1.25 (1.02–1.54), 1.23 (1.01–1.51), respectively, and corresponding figures for high fasting insulin were 1 (reference), 0.98 (0.80–1.19), 1.12 (0.91–1.38), and 1.29 (1.06–1.57), respectively. Subcutaneous fat area was not associated with EDS. CONCLUSIONS: Results suggest that EDS is related to visceral, but not subcutaneous, fat accumulation and insulin resistance in middle-aged Japanese men.